KPPBC TMP Juanda Policy in Achieving Revenue Target as a Impact of De Minimis Value: Kebijakan KPPBC TMP Juanda dalam Mencapai Target Penerimaan Sebagai Dampak Adanya De Minimis Value - Muhammad Fauzi Ramadlan; Akhmad Mulyadi (Academia Open, 2024)
Background: The implementation of the de minimis value rule, which sets a threshold for import duty exemptions on small shipments, significantly influences national trade dynamics and fiscal policies. Despite global integration and economic transactions escalating, effective customs regulations remain pivotal for controlling import activities and enhancing revenue. Knowledge Gap: Prior research has primarily focused on the implications of the de minimis rule on import volumes and compliance, leaving a gap regarding its impact on revenue targets and administrative practices at the customs office level. Aims: This study aims to explore the strategies employed by KPPBC TMP Juanda in achieving revenue targets influenced by the de minimis value policy. Methods: Utilizing qualitative research methods, including interviews, observation, and documentation, this research engages directly with three customs officials at KPPBC TMP Juanda, analyzing data with NVivo12Plus. Results: The findings indicate that while the de minimis value does not control the surge in import activities, it assists in increasing revenue and meeting fiscal targets. Novelty: This study provides new insights into how customs policies adapted at the local office level can contribute to national fiscal strategies under global trade pressures. Implications: The outcomes underscore the necessity for continuous policy evaluation to balance trade facilitation with fiscal responsibility, suggesting enhancements in customs operations to optimize revenue without stifling economic growth. Highlights: Customs Strategy: De minimis value adjustments reflect local customs alignment with fiscal goals. Revenue Impact: The rule boosts revenue without curbing import volumes. Policy Review: Highlights the need for continual policy optimization to balance trade and revenue. Keywords: Policy, Revenue Target, De Minimis Value